2020
DOI: 10.3389/fpls.2020.587610
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage Polysaccharide Composition and Exudation in Maize From Contrasting Climatic Regions

Abstract: Mucilage, a gelatinous substance comprising mostly polysaccharides, is exuded by maize nodal and underground root tips. Although mucilage provides several benefits for rhizosphere functions, studies on the variation in mucilage amounts and its polysaccharide composition between genotypes are still lacking. In this study, eight maize (Zea mays L.) genotypes from different globally distributed agroecological zones were grown under identical abiotic conditions in a randomized field experiment. Mucilage exudation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 66 publications
(106 reference statements)
3
31
0
Order By: Relevance
“…The properties of plant-derived mucilages depend on their chemical structures and compositions. In recent years, extensive efforts have been made to link the quality (nutritional value, functional and technological features) of plant mucilages to their chemical compositions [2,[53][54][55]. The important attributes of mucilages and factors impacting their quality are summarized in Figure 3.…”
Section: Chemical Characterization Of Mucilagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of plant-derived mucilages depend on their chemical structures and compositions. In recent years, extensive efforts have been made to link the quality (nutritional value, functional and technological features) of plant mucilages to their chemical compositions [2,[53][54][55]. The important attributes of mucilages and factors impacting their quality are summarized in Figure 3.…”
Section: Chemical Characterization Of Mucilagesmentioning
confidence: 99%
“…"Green" techniques used for the extraction of plant biological compounds have recently received more attention, improving extraction yield, reducing process time and the need for chemicals, and lowing costs. Further research in needed on optimizing the parameters of mucilage extraction from plants [2,[53][54][55].…”
Section: Function Of Mucilages In Plantsmentioning
confidence: 99%
“…A reporter-gene approach confirmed that polygalacturonase is highly expressed in maize exudates from monoculture or in association with bean (Figure 7A). Sugars such as galactose, fucose, mannose, arabinose, xylose, and glucose together with uronic acids like galacturonic acid and glucuronic acid are the main components of mucilage (Nazari et al, 2020). Genes for transporters and enzymes for metabolism of these sugars were expressed in maize exudates, so Ch24-10 perhaps consumes them as carbon sources once they are released from plant polymers or directly from the exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Mucilage increases the water content of the rhizosphere, connects soil particles, increases the soil liquidphase connectivity, and facilitates root water uptake under drought, due to its high viscosity and low surface tension (Young, 1995;Carminati et al, 2010;Ahmed et al, 2015;Benard et al, 2019;Zarebanadkouki et al, 2019). Mucilage absorbs 27-589 times more water than its dry weight (McCully and Boyer, 1997;Huang and Gutterman, 1999;Capitani et al, 2013;Nazari et al, 2020), which is considerably higher than the amount of water absorbed by a similar quantity of EPS. The binding of negatively charged uronic acids to Ca 2+ governs hydrationdehydration dynamics in biogels (Dean et al, 2007;North et al, 2014;Brax et al, 2019).…”
Section: Biogels As Microbial Habitatsmentioning
confidence: 99%